Mentoring sebagai Praktik Berbagi Pengetahuan dalam Pengembangan Kapasitas Sosial Anggota Baru Mahaperan - Febrian Gibran Juliansyah; Rully Khairul Anwar; Samson CMS (Yayasan pendidikan dzurriyatul Quran, 2026)
Organizations with a membership system face challenges in maintaining the continuity of knowledge, values, and social practices during membership turnover. This study aims to examine mentoring as a knowledge-sharing practice in developing the social capacity of new members at Mahaperan Bandung. The study employed a qualitative approach through a case study method. Data were obtained through in-depth interviews with five mentors and five new members, observations of organizational activities, and documentation. The data were then analyzed through data reduction, data presentation, and conclusion drawing. The results demonstrate that mentoring serves as a bridge for knowledge sharing, internalization of organizational values, and the creation of social relationships through formal learning spaces, informal interactions, practical activities, and periodic evaluations. The success of this process is influenced by trust, a family culture, two-way communication, frequency of meetings, alignment of meanings, and organizational support. The impact is evident in the development of communication skills, collaboration skills, empathy, trust, active participation, and a sense of belonging among new members. This study demonstrates that mentoring is not merely personal development, but rather a mechanism for targeted knowledge sharing to enhance the social capacity of student organizations.